Trends in Bicuspid Aortic Valve–Attributable Death in the United States From 2010 to 2020 - Zuin, Marco; Campia, Umberto; De la Cruz, Kim I.; Singh, Michael; Piazza, Gregory (Journal of the American Heart Association, 2025)
Population-based data on bicuspid aortic valve (BAV)-attributable mortality trends in the United States are limited. This study assessed trends in BAV-attributable death in the United States from 2010 to 2020, evaluating differences by sex, ethnicity, urbanization, and census region. Data were extracted from the Centers for Disease Control and Prevention's Wide-Ranging Online Data for Epidemiologic Research system. Trends in age-adjusted mortality rates per 100 000 population were analyzed using JoinPoint regression to calculate average annual percentage change and annual percentage change, with corresponding 95% CIs. From 2010 and 2020, 3537 deaths were attributable to BAV, corresponding to 11.7 deaths per 100 000 population. Age-adjusted mortality rates increased linearly, with an average annual percentage change of +4.6% (95% CI, 2.8-6.5; 0.001). Women experienced a steeper increase (average annual percentage change, +8.0% [95% CI, 3.3-12.9]; 0.001) compared with men (average annual percentage change, +5.3% [95% CI, 3.6-7.0]; 0.001). Mortality trends were more pronounced among Hispanic/Latinx individuals and those aged <65 years. No significant differences between urban and rural settings were observed ( 0.35), while the South accounted for the highest proportion of deaths (31.1%). BAV-attributable mortality has increased over the past decade, with significant disparities by sex, age, and region. These results highlight the critical importance of developing targeted health care approaches and enhancing strategic management techniques to address specific population BAV-related health concerns.